Capital Structure Determinants of Sharia-Compliant and Non-Compliant Companies in the Food and Beverage Sector - ARIF; Mohammad Nofal; Cici Rianty K. Bidin; Ayu Putri Utami (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of profitability, tangibility, Tobin’s Q, and firm size on the capital structure of Sharia and non-Sharia food and beverage companies listed on the Indonesia Stock Exchange during 2020–2025. Using purposive sampling, the study analyzed 240 observations through panel data regression with the Random Effects Model. The results show that profitability negatively affects capital structure, while tangibility and Tobin’s Q have positive effects. Firm size has no significant effect. In Sharia companies, profitability and Tobin’s Q are significant, whereas in non-Sharia companies, only tangibility significantly affects capital structure. Keywords: Capital Structure; Sharia Companies; Profitability; Tangibility; Tobin's Q; Firm Size